Sports Orthopedics - Neumayr L; Schmitt H (Dynamic Media Sales Verlag, 2019)
Objective: To assess injury incidence, nature, severity, and mechanisms in amateur and professional polo players in Germany and Switzerland during the 2017 season.Methods: Questionnaire-based survey, where players were interviewed by the first author and injuries over the last two years recorded. The study was conducted from May-July 2017. Players were interviewed during tournaments and practice matches.Results: A total of 103 polo players were interviewed. Forty percent (n=41) of the players experienced a total of 55 injuries. The injury rate was 5.3-6.1/1000 player-game hours. Sixty-seven percent of all injuries were classified as major. Trauma was the main (84%; 46 cases) cause of injury. Most cases (42%) involved the upper extremity, followed by the lower extremity in 14 (25%) cases. The trunk was affected in 12 cases (22%) and the head in 6 (11%). Overall, a typical pain pattern after playing polo (without missing play) was observed in the lumbar spine, groin, and hitting arm.Conclusions: Although the injury rate was low, the severity was quite high. Typical injury and overuse patterns are presented in this study. Life-threatening injuries do occur, and medical staff trained in trauma management should be present at polo matches. Safer helmets according to the newest standards should be worn and the face should be protected to avoid fatal injuries.Clinical Relevance: Polo is a dangerous team sport that can lead to major injuries and suitable preventive methods should be developed.KEY WORDS: Polo, Injury Rate, Injury Severity, Polo Riders